Experimental investigation to mitigate aeolian erosion via biocementation employed with a novel ureolytic soil isolate - Dubey, Anant Aishwarya; Devrani, R.; Ravi, K.; Dhami, Navdeep; Mukherjee, Abhijit; Sahoo, L. (2021)
Aeolian ecosystems suffer severe land degradation due to wind erosion. This study presents the erosion mitigation via bio-cementation technique for the soil collected from Jaisalmer region of the Thar Desert of India. Most of the previous studies considered conventional microbe Sporosarcina pasteurii for aeolian erosion mitigation. Alternatively, as the soils containing vegetation are rich in microbial diversity, this study presents isolation and characterisation of a novel urease-positive microbial strain from a soil slope, which is later utilised for the aeolian-erosion mitigation. The desert sand was subjected to biocementation treatment using the isolated microbe and various molar concentrations (M) of cementation solution, ranging from 0.25 M to 1 M. The engineering properties of the biocemented sand such as coefficient of permeability (k), unconfined compressive strength (UCS), and erodibility was investigated. The soil erosion test was conducted in a lab-scale wind tunnel to investigate parameters such as soil mass loss and threshold detachment velocity. The investigation revealed a decrease of one order in the magnitude of the permeability coefficient with 1 M biocementation treatment. A high UCS value of around 1 MPa was observed with a low calcium carbonate content of 1.3% precipitated with 0.5 M cementation solution treatment. The erosion resistance is observed to be maximum with 1 M cementation solution treatment withstanding the maximum wind velocity above 55 km/h. With lab-scale investigation, this study confirms drastic improvement in soil erodibility resistance with biocementation using the isolated microbe and encourages field trial for protecting the desert ecosystem from severe erosion.